Zinc oxide nanoparticles enhances germination performance of wheat (Triticum durum L.) seeds under individual and combined salinity and copper treatments - Chokri Zaghdoud; Kamel Nagaz (Journal of Oasis Agriculture and Sustainable Development, 2022)
In oasis areas, with the depletion of fresh water resources and the use of underground water and industrial wastewater for irrigation, agriculture is under the cumulative harmful effects of multiple abiotic factors such as salinity and heavy metals. Under these conditions, a new strategy to improve crop production is urgently required. Here, we evaluate the potential of zinc oxide nanoparticles (ZnO-NPs) (0, 50 mg/L) to attenuate single and interactive effects of 10-days exposure to salinity (0, 50 mM NaCl) and copper (0, 50 mg/L CuSO4) treatments on the germination performance of wheat (Triticum durum L. Desf., ‘Chili’) seeds. Results showed that, in the absence of ZnO-NPs, exposure to salinity or copper alones significantly (P < 0.05) inhibits the germination process. The combined exposure to salinity and copper, aggravates the inhibitory effects on seeds germination. In contrast, addition of ZnO-NPs significantly improved wheat germination in control conditions, and attenuates the harmful effects of single and combined NaCl and CuSO4. The potential mechanism of the preventive effect of ZnO-NPs might involve a competitive replacement of Cu2+ accumulation by which of Zn2+. It is concluded that ZnO-NPs improves the germination of wheat seeds in oasian lands suffering from hypersalinity and copper soil’s accumulation, thus ameliorates their productivity.